2017
DOI: 10.1017/wet.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Mowing: An Option for Sustainable Weed Management in Young Citrus Orchards

Abstract: The citrus yield in Brazil is not ranked among the best in the world, potentially due to inadequate management by citrus growers. The low adoption of conservation agriculture (CA) techniques and the improper application of herbicides are also well-known problems. Thus, this study evaluated the use of CA techniques, and twoUrochloaspecies (ruzi grass and signal grass) were used as cover crops. Two different types of mowers (ecological, EM; conventional, CM) launched the mowed biomass into different positions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 16 publications
(17 reference statements)
0
36
0
Order By: Relevance
“…Pacheco et al (2016) studied the use of cover crops such as U. ruziziensis in no-tillage and conventional systems with soybean, corn and rice crops in the cerrado of Piauí and demonstrated significant reductions in the emergence and accumulation of weeds. Martinelli et al (2017) studied the effect of two species of Urochloa on the Citrus and found that Urochloa as a cover is a good option for the sustainable and integrated management of weeds. Nepomuceno et al (2017) studied the effect of U. ruziziensis when used as a vegetative cover in the cultivation of transgenic soybeans, and found that extracts collected from U. ruziziensis contained substances which can control the growth of weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Pacheco et al (2016) studied the use of cover crops such as U. ruziziensis in no-tillage and conventional systems with soybean, corn and rice crops in the cerrado of Piauí and demonstrated significant reductions in the emergence and accumulation of weeds. Martinelli et al (2017) studied the effect of two species of Urochloa on the Citrus and found that Urochloa as a cover is a good option for the sustainable and integrated management of weeds. Nepomuceno et al (2017) studied the effect of U. ruziziensis when used as a vegetative cover in the cultivation of transgenic soybeans, and found that extracts collected from U. ruziziensis contained substances which can control the growth of weeds.…”
Section: Introductionmentioning
confidence: 99%
“…Weed control is important in young orchards where canopy shadowing is low and weeds are not naturally suppressed. Furthermore, competition for water and nutrients is high during this period [13]. The depositing of Urochloa spp.…”
Section: Soil Microbiological Qualitymentioning
confidence: 99%
“…The use of the herbicide glyphosate in citrus rows is a common practice in citrus orchards [13,14]. However, despite its biodegradation in soil, its effect on the shikimic acid pathway can cause disturbances in the cellular metabolism of bacteria, fungi, plants, and other organisms [15], and can harm the composition of the soil microbial community [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The State of São Paulo (SP) accounts for~77% of the national production of orange (Citrus sinensis (L.) Osbeck), being the main exporter of concentrated orange juice [2]. However, the yield of citrus fruit is not the best in the world, mainly due to improper management of the plantations by growers [3]. The average orange yield is 27.6 tons ha −1 , occupying the 13th world rankings [4].…”
Section: Introductionmentioning
confidence: 99%